2019
DOI: 10.1183/23120541.00171-2018
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of α1-antitrypsin deficiency in Europe: an expert survey

Abstract: Despite recent improvements, α1-antitrypsin deficiency (AATD) remains a rarely diagnosed and treated condition. To assess the variability of AATD diagnosis/treatment in Europe, and to evaluate clinicians’ views on methods to optimise management, specialist AATD clinicians were invited to complete a web-based survey.Surveys were completed by 15 physicians from 14 centres in 13 European countries. All respondents perceived the AATD diagnosis rate to be low in their country; 77% of physicians believed that ∼15% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(73 citation statements)
references
References 41 publications
1
71
0
1
Order By: Relevance
“…A recent European expert survey has shown that provision of AAT therapy is highly variable throughout Europe [45]. France and Germany were reported to have the highest proportions of diagnosed AATD patients receiving AAT therapy (60%); in Spain, ∼20% of patients receive treatment with AAT.…”
Section: Lung Transplantationmentioning
confidence: 99%
“…A recent European expert survey has shown that provision of AAT therapy is highly variable throughout Europe [45]. France and Germany were reported to have the highest proportions of diagnosed AATD patients receiving AAT therapy (60%); in Spain, ∼20% of patients receive treatment with AAT.…”
Section: Lung Transplantationmentioning
confidence: 99%
“…Vorerst ist die CT-Densitometrie allerdings noch wissenschaftlichen Fragenstellungen vorbehalten. FEV 1 und DLCO sind laut einer aktuellen Umfrage nach wie vor die am meisten angewandten Messparameter zur Verlaufsbeurteilung der AATM-Erkrankung [28].…”
Section: Monitoring Von Individuen Und Patienten Mit Aatmunclassified
“…Given the range of tests available to clinicians, efforts towards the standardization of laboratory diagnostics for AATD are under way and will be discussed later. 10,11 Underdiagnosis, a continuing issue in the field with reports of delays of up to 6 years before a diagnosis of AATD is confirmed, is of particular significance as diagnostic delays have been associated with greater symptom burden at the time of eventual diagnosis. 12 This may result from reluctance of the patient to seek medical attention, lack of health care practitioner awareness, and failure to conduct AATD testing when warranted.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a program in Germany successfully increased diagnosis rates of AATD by combining an educational campaign with cost-free genetic testing. 17 Another factor is the lack of uniform reimbursement for AAT augmentation therapy, the only available diseasemodifying pharmacological intervention for AATD, 6,10,18 which likely limits prioritization of AATD testing in countries where treatment is not available. 19 Testing should be done regardless of the availability of specific treatment since preventative measures such as smoking cessation, evaluation of occupational exposures, and monitoring for other associated pathologies (eg, liver disease) may significantly modify the clinical course of affected individuals.…”
Section: Introductionmentioning
confidence: 99%